Correlation between Height And Percent Body Fat with Musculoskeletal Fitness at Adolesence - Rahmayanti, Kamilia; Sudiarti, Trini (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2019)
This study aims to determine the relationship between energy and nutrients intake, body weight, height, BMI-for-Age, percent body fat, physical activity, and socioeconomic status with musculoskeletal fitness. This study used a cross-sectional design. A total of 151 students from 5 Bekasi High School class X and XI were included in this study. Food intake was measured using 2x24 hours food recall, physical activity using Global Physical Activity Questionnaire (GPAQ), anthropometri by direct measurement, and socioeconomic using Family Affluence Scale (FAS) questionnaire. Regression analysis for bivariate and Anova for analysis of socioeconomic status.  The results of this study showed that there were a significant relationship between energy (p=0,001) and nutrients intake (carbohydrate p=0,037; protein (p=0,001; fat (p=0,001), body weight (p=0,002), height (p=0,001), percent body fat (p=0,001), and physical activity (p=0,001) with musculoskeletal fitness before controlled by sex. After stratification analysis by sex, there was a significant relationship between height and percent body fat with musculoskeletal fitness(p<0,005), but only found in male students.